Penegakan Hukum Tindak Pidanai Penangkapan Ikan Menggunakan Jaring Trawl (Illegal Fishing) di Wilayah Perairan Jawa Timur - I Nengah Budiarta; Hervina Puspitosari (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Illegal fishing is a form of criminal activity in the field of fishing. Cases of illegal fishing in the eastern Java region in the period 2021-2023 saw a decrease in cases, but by the end of the case does not belong to the rise. The purpose of this research is to find out the form of law enforcement of illegal fishing using trawl nets in the territory of eastern Java waters by the East Java Police Water Police Directorate. The method used is empirical yuridic method with data sources derived from primary data obtained through interviews with Subditgakkum Ditpolair Polda Jatim and secondary data. The results of this study are that the law enforcement carried out by Ditpolair Polda Jatim is still not maximum enough because of several factors, such as uncertain weather, bureaucratic communication with stakeholders that takes quite a long time, the main tools of the defence system are still not adequate, inequality of resources, difficulty identifying vessels that have been engaged in illegal fishing, and the factor of public awareness is said to be still low to the law. However, each of these obstacles has had efforts to overcome it.